Hollow tire-shaped carbon material composite transition metal sulfur selenide electrode material
Through the composite material of the hollow tire-like carbon skeleton derived from Aspergillus niger spores and transition metal sulfide selenide nanosheets, the ion transport and structural stability of the electrode material in sodium ion batteries is solved, and the electrochemistry with high capacity and long life is achieved Performance, suitable for commercial applications of sodium ion batteries.
Patent Information
- Application Number
- CN202411329996.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-28
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The existing transition metal chalcogenide electrode materials have problems such as slow ion transfer rate, severe volume expansion and ultra-thin nanosheet stacking and structural collapse caused by repeated insertion of sodium ions in sodium ion batteries, which limits their performance in large-scale applications. and lifespan.
The composite material of a hollow tire-like carbon skeleton derived from Aspergillus niger spores and transition metal sulfide selenide nanosheets is coated with a carbon layer derived from glucose or polypyrrole, and is prepared by high-temperature carbonization and hydrothermal reaction to form ANDC@MSSe@ C structure to improve conductivity and structural stability.
The electrode material with high reversible capacity and long cycle life at ultra-high magnification is realized, which suppresses structural damage during sodium ion deintercalation, improves the diffusion kinetics and electrochemical properties of Na+, adapts to volume expansion, and extends the battery. service life.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery materials, and in particular relates to an electrode material of a hollow tire-shaped carbon material composited with transition metal sulfide selenide. Background Art
[0002] Lithium-ion batteries (LIBs) have attracted extensive research interest worldwide since their first commercialization in 1991. With their high energy density, strong safety, and long cycle life, LIBs have flourished in emerging applications. However, the scarcity and uneven distribution of lithium resources make it difficult to continuously meet the demand for large-scale energy storage systems. To alleviate this situation, the development of an alternative rechargeable battery system has attracted widespread attention. Among the many candidate batteries, sodium-ion batteries (SIBs) stand out with their advantages such as abundant sources, suitable redox potential, and low cost. They are considered to be a better alternative to lithium-ion batteries and a key technology for large-scale energy storage technology. In addition, cheaper, lighter, and more abundant aluminum (Al) foil can be used as a current collector for SIBs, while copper (Cu) is the only choice for LIBs, which means that SIBs have lower costs and greater commercial potential. Despite their many attractive advantages, SIBs also face many daunting challenges. The ionic radius of Na (Na + for Li + for ) and molar mass (22.99 gmol for Na -1 , Li is 6.94 g mol -1 ) are significantly larger than Li, which is not conducive to the diffusion kinetics of sodium ions during the sodiumation / de-sodiumation process and the structural stability of the electrode materials. Unfortunately, this means that most traditional electrode materials used in LIBs cannot be used in SIBs. Therefore, the key technology for developing SIBs lies in the development of electrode materials with good electrochemical properties.
[0003] In the past few years, the research on positive electrode materials for SIBs has made encouraging progress, including layered materials, polyanionic compounds and Prussian blue analogs. However, the development of negative electrode materials with low electrochemical reaction platform, relatively high reversible capacity and stable structure is still insufficient. So far, the commonly used anode materials for SIBs include carbonaceous materials, titanium materials, alloy materials, metal oxides / sulfides / selenides and organic materials. Among them, metal sulfide compounds with layered and non-layered structures have become a research hotspot due to their diverse material types. In particular, layered metal sulfides (Transition metalsulfide, TMS) have the advantages of abundant reserves, low cost, stable performance and high theoretical capacity. In addition, due to their multi-electron redox reactions and easy breakage of MS bonds (M represents metal), they show higher theoretical capacity and faster ion diffusion rate. For example, the invention patent CN110600275B discloses a preparation method and application of a metal sulfide / carbon composite electrode material, in which carbon and metal sulfide are uniformly compounded, with good conductivity and a stable bowl-shaped structure. Invention patent CN112349889B discloses a method for preparing transition metal sulfide nanocomposite electrode materials. By synthesizing MOFs precursors and using them as hard templates, the structural characteristics of MOFs precursors are maintained while preparing metal sulfides through one-step carbonization and sulfurization. However, most of them still suffer from inherent low conductivity and severe volume expansion during long-term cycles, which will lead to poor rate performance and rapid capacity decay. In order to solve these thorny problems, considerable efforts have been made to construct exquisite nanostructures. Specifically, the introduction of exogenous anionic ligands to form single-phase ternary metal disulfides plays an atomic-level interface engineering role, providing a promising way to adjust their physicochemical properties. Selenium (Se) has similar chemical properties to sulfur, but has a smaller band gap and a larger atomic radius. Therefore, Se atoms are doped into the layered TMSs lattice to form S 2-x Se x Interlayer ligands can improve conductivity, expand interlayer spacing, enrich anion defect sites, and enhance Na + On the other hand, TMS with hollow (inner cavity) structure and carbon modification can accommodate Na + The volume expansion during insertion maintains structural stability and improves conductivity, thereby ensuring a longer service life and promoting Na +storage capacity. However, the existing composite layered structured metal disulfide electrode materials still have undesirable results such as repeated insertion of sodium ions resulting in highly stacked, agglomerated and even structural collapse of ultra-thin nanosheets, which limits their large-scale application in SIBs and unsatisfactory performance. In addition, most of the metal disulfides containing polyanionic ligands reported so far involve relatively complex synthesis processes, expensive instruments, and uncontrollable anion concentrations. Therefore, it is a very urgent challenge to develop an efficient and scalable method to prepare transition metal-based sulfide selenides with fast charge transport properties and strong structures on a large scale. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide an electrode material of a hollow tire-shaped carbon material composited with a transition metal sulfide selenide, which has an ultra-high reversible capacity, an ultra-long cycle life and good structural stability at an ultra-high rate, and solves the problems of existing metal sulfide electrode materials such as slow ion transfer rate, severe volume expansion, and repeated insertion of sodium ions resulting in high stacking, agglomeration and even structural collapse of ultra-thin nanosheets.
[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: an electrode material of a hollow tire-shaped carbon material composite transition metal sulfide selenide, comprising a carbon skeleton with a three-dimensional hollow tire-shaped structure derived from Aspergillus niger spores and a transition metal sulfide selenide nanosheet material loaded on the carbon skeleton, and the outer layer of the nanosheet material is coated with a carbon layer, and the outer coated carbon layer is a carbon layer derived from glucose (G), polypyrrole (PPy) or polydopamine (PDA), so that the outer coated carbon layer can effectively protect the structural integrity of the material during the sodium ion deintercalation process and provide better conductivity; the electrode material has a chemical composition represented by ANDC@MSSe@C, wherein ANDC is a hollow tire-shaped carbon skeleton derived from Aspergillus niger spores (Aspergillus Niger spores derived carbon), and M is a metal element Sn, Mo or W. Compared with the MS band, the M-Se bond strength is weaker and is easily broken in the conversion reaction, and in the process of sodium ion deintercalation, it will limit the formation of sodium polysulfide molecules, further enhancing the Na + Reaction kinetics and reversible deintercalation of sodium ions. Preferably, the M is a metal element Sn, and the outer coated carbon layer is a glucose derived carbon layer.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned hollow tire-shaped carbon material composite transition metal sulfide selenide electrode material, comprising the following steps:
[0007] 1) ultrasonically treating Aspergillus niger spores in deionized water, washing them, and drying them;
[0008] 2) subjecting the Aspergillus niger spores obtained in step 1) to high-temperature carbonization treatment in a tubular furnace with a protective atmosphere, and cooling naturally after the reaction is completed to obtain a hollow tire-shaped carbon material ANDC derived from the Aspergillus niger spores;
[0009] 3) placing the ANDC material obtained in step 2) in a solution containing a sulfur source and one of a tin source, a molybdenum source and a tungsten source and continuously stirring to obtain a mixed solution, then transferring the mixed solution to a high-pressure reactor for a high-temperature reaction, cooling naturally after the reaction, and then washing the product with deionized water and anhydrous ethanol for multiple times and drying to obtain an ANDC@MS2 composite material.
[0010] 4) adding the ANDC@MS2 composite material obtained in step 3) to an aqueous solution containing glucose, stirring continuously to obtain a suspension, and then transferring the suspension to a high-pressure reactor for hydrothermal reaction, and cooling naturally after the reaction to obtain the product ANDC@MS2@G; or adding the ANDC@MS2 composite material obtained in step 3) to an aqueous solution containing dopamine or pyrrole, stirring continuously at room temperature to cause a polymerization reaction to obtain the product ANDC@MS2@PPy or ANDC@MS2@PDA;
[0011] 5) The product obtained in step 4) is washed with deionized water and anhydrous ethanol for multiple times and dried, and then the dried product is placed in a tube furnace with a protective atmosphere for high-temperature carbonization treatment. After the reaction is completed, the temperature is naturally lowered to obtain ANDC@MS x @C (x = 1 or 2) composite material; when M is W and Mo, X is 2, that is, the loaded WS2 and MoS2 are unchanged after carbonization annealing; when M is Sn, X is 1, that is, the loaded SnS2 is changed into SnS after carbonization annealing.
[0012] 6) ANDC@MS prepared in step 4) x @C and selenium powder are placed in a porcelain boat respectively and wrapped with a piece of tin foil, and then selenized in a protective atmosphere. After the reaction is completed, the temperature is naturally lowered to obtain the hollow tire-shaped carbon material composite transition metal sulfide selenide electrode material ANDC@MSSe@C.
[0013] Furthermore, the high temperature carbonization treatment in step 2) is carried out by heating the temperature to 500-1000°C at a heating rate of 1-20°C / min and then keeping the temperature for 0.5-10h; the high temperature reaction in step 3) is carried out at a temperature of 180-220°C for 12-24h.
[0014] Furthermore, in step 3), the tin source is tin tetrachloride or stannous chloride; the molybdenum source is sodium molybdate or ammonium molybdate; the tungsten source is sodium tungstate or ammonium tungstate; the sulfur source is sublimated sulfur, thioacetamide or thiourea; when the tin source is added to the mixed solution, the solution is an organic solvent, and the organic solution is ethylene glycol or isopropanol; when the molybdenum source or tungsten source is added to the mixed solution, the solution is deionized water.
[0015] Furthermore, in step 3), the amount of ANDC added to the mixed solution is 1.0-10 mg / mL, and the molar ratio of the tin source, molybdenum source or tungsten source to the sulfur source is 1:2-1:4.
[0016] Furthermore, in step 4), the concentration of glucose, dopamine or pyrrole is 0.02-0.1 M; the temperature of the hydrothermal reaction is 150-200° C., and the time is 6-24 h.
[0017] Furthermore, the high temperature carbonization treatment in step 5) is carried out by heating the temperature to 500-800° C. at a heating rate of 1-10° C. / min and then keeping the temperature for 1-6 hours.
[0018] Furthermore, the selenization treatment in step 6) is performed by heating the temperature to 350-450°C at a heating rate of 1-5°C / min and then keeping the temperature for 0.5-5h; the ANDC@MS x The mass ratio of @C to selenium powder is 1:1 to 1:10.
[0019] Furthermore, the protective atmosphere is argon or nitrogen; and the drying is carried out at 25 to 90° C. for 8 to 12 hours.
[0020] Another object of the present invention is to provide the use of the above electrode material or the electrode material prepared by the above method in a sodium ion battery.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The hollow tire-shaped carbon material composite transition metal sulfide selenide electrode material provided by the present invention utilizes a hollow tire-shaped carbon skeleton derived from Aspergillus niger spores to composite layered ternary transition metal sulfide selenide nanosheets. The hollow tire-shaped carbon skeleton derived from Aspergillus niger spores in this structure can effectively induce the uniform growth of metal sulfide selenide nanosheets, thereby effectively inhibiting the destruction, crushing and agglomeration of the metal sulfide selenide structure existing in the repeated de-sodiumization process of sodium ions during the charge and discharge process, thereby exhibiting a high specific volume and good cycle life. At the same time, with the uniform substitution of Se atoms for S atoms, the abundant crystal defects formed in situ inside the metal sulfide selenide nanosheets can not only serve as a convenient Na + Diffusion sites to ensure Na +The rapid insertion process of M can effectively reduce the Gibbs free energy and act as a propellant for the nucleation process of the intermediate product in the initial transformation state, leading to the final product M 0 (M is Sn, Mo, W), Na2S, and Na2Se. In addition, due to the rich interface between the final product Na2S and Na2Se and the low Na + The induction of diffusion barriers greatly improves the diffusion kinetics of Na ions between the intermediates of the conversion-alloying reaction. Most importantly, M 0 The high-density grain boundaries of the Na2S / Na2Se intermediates help stabilize the active components and limit the volume change, thereby effectively inhibiting the M 0 agglomeration, improving the integrity of the layered structure, and ultimately ensuring that the reversibility of the conversion-alloying reaction is improved during long-term cycles. Therefore, the electrode material of the present invention has a high specific capacity, and still has good retention after 2000 cycles, showing good and cyclically stable electrochemical performance, and still has good structural stability and cycle life at ultra-high rates. The present invention solves the problems of slow ion transfer rate, severe volume expansion, and repeated insertion of sodium ions in existing transition metal sulfide electrode materials, resulting in high stacking, agglomeration, and even structural collapse of ultra-thin nanosheets, and has good application prospects.
[0023] 2. The novel hollow tire-shaped carbon material composite transition metal sulfide selenide electrode material prepared by the present invention is prepared and synthesized by means of hydrothermal reaction, high-temperature carbonization and selenization treatment, etc., using carbon skeleton derived from Aspergillus niger spores as the main raw material. Compared with metal sulfide solid solutions synthesized by other synthesis methods, the present invention has low raw material cost, simple process, low energy consumption, and easier reaction conditions, and can be mass-produced, which is convenient for commercial application.
[0024] 3. The hollow tire-shaped carbon material composite transition metal sulfide selenide electrode material of the present invention exhibits ultra-long cycle life, large reversible specific capacity and excellent rate performance; and the full battery assembled with ANDC@SnSSe@C electrode material and positive electrode material Na3V2(PO4)3@C has an initial coulombic efficiency of more than 100% and a capacity retention rate of more than 78.8%, and also exhibits good cycle life and rate performance, indicating that the ANDC@SnSSe@C composite electrode material of the present invention has shown great application prospects in sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 : electron microscope images of Aspergillus niger spores and hollow tire-shaped carbon materials in Example 1; a and b are scanning electron microscope images of Aspergillus niger spores, c and d are scanning electron microscope images of hollow tire-shaped carbon materials; e and f are transmission electron microscope images of hollow tire-shaped carbon materials.
[0026] Figure 2 Scanning electron microscope images of ANDC@SnS2 and ANDC@SnS@C in Example 1; a and b are ANDC@SnS2, and c and d are ANDC@SnS@C.
[0027] Figure 3 The scanning electron microscope (a, b) and transmission electron microscope (c, d) images of the ANDC@SnSSe@C electrode material prepared in Example 1.
[0028] Figure 4 This is the X-ray diffraction pattern of the ANDC@SnSSe@C electrode material prepared in Example 1.
[0029] Figure 5 (a) Thermogravimetric analysis diagram and (b) electron paramagnetic resonance spectrum of ANDC@SnSSe@C electrode material prepared in Example 1.
[0030] Figure 6 This is the X-ray photoelectron spectrum of the ANDC@SnSSe@C electrode material prepared in Example 1.
[0031] Figure 7 CV curves of batteries assembled with ANDC@SnSSe@C electrode materials at different scan rates.
[0032] Figure 8 This is the rate performance diagram of the battery assembled with ANDC@SnSSe@C electrode material.
[0033] Fig. 9 To prepare a half-cell with ANDC@SnSSe@C electrode material at 1.0A g -1 Charge and discharge curves under current density (a) and cycle stability test (b).
[0034] Fig.10 The half-cell prepared with ANDC@SnSSe@C electrode material at 20.0Ag -1 Cyclic stability test at different current densities.
[0035] Fig.11 Electrochemical performance test of full battery prepared with ANDC@SnSSe@C electrode material; (a) at 1.0A g -1 (a) Cyclic voltammetry curve under current density, (b) cycle stability test, (c) charge and discharge curves at different current densities, and (d) rate performance test. DETAILED DESCRIPTION
[0036] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, but the embodiments are not intended to limit the present invention. Experimental methods without specific conditions in the preferred embodiments are usually carried out under conventional conditions or under conditions recommended by the reagent manufacturer.
[0037] 1. A method for preparing an electrode material of a hollow tire-shaped carbon material composite with a transition metal sulfide selenide
[0038] Example 1
[0039] 1) Preparation of hollow tire-shaped carbon materials
[0040] The Aspergillus niger spores were ultrasonically treated in deionized water, cleaned, and dried. 5 g of the dried Aspergillus niger spores were placed inside a porcelain boat and wrapped with tin foil, and then transferred to a high-temperature tube furnace protected by Ar atmosphere, and then the temperature was raised to 700°C at a heating rate of 5°C / min, and kept for 2 hours, and finally cooled naturally to room temperature to obtain the Aspergillus niger spore-derived hollow tire-shaped carbon material (ANDC).
[0041] 2) Preparation of ANDC@SnS2 precursor
[0042] 0.385 g of SnCl2·2H2O and 0.056 g of sublimed sulfur were dissolved in 70 ml of ethylene glycol solution, and stirred evenly for half an hour to obtain a mixed solution; then 0.3 g of ANDC prepared in step 1) was added to the mixed solution, and ultrasonicated for half an hour to obtain a suspension; the suspension was then transferred to a 100 ml high-pressure reactor and reacted at 180°C for 12 hours. After the reaction was completed, the suspension was naturally cooled, and the obtained product was washed three times with deionized water and anhydrous ethanol in turn, and dried in a vacuum drying oven at 80°C for 8 hours to obtain ANDC@SnS2 material.
[0043] 3) Preparation of ANDC@SnS2@G composites
[0044] 0.3 g of ANDC@SnS2 precursor prepared in step 2) was dispersed in 60 ml of 0.075 M glucose aqueous solution and ultrasonically stirred for 30 min. Then, it was transferred to a 100 ml high-pressure reactor and reacted at 180 °C for 12 h. After the reaction was completed, it was naturally cooled. The product was washed three times with deionized water and anhydrous ethanol in sequence, and dried in a vacuum drying oven at 80 °C for 8 h to obtain ANDC@SnS2@G material.
[0045] 4) Preparation of ANDC@SnS@C composites
[0046] The ANDC@SnS2@G material obtained in step 3) was placed inside a porcelain boat and wrapped with tin foil, and then transferred into a high-temperature tube furnace protected by Ar atmosphere, and then the temperature was raised to 500°C at a heating rate of 2°C / min and kept for 2h, and finally naturally cooled to room temperature to obtain an ANDC@SnS@C composite material.
[0047] 5) Preparation of ANDC@SnSSe@C composites
[0048] 0.2 g of ANDC@SnS@C obtained in step 4) and 0.8 g of selenium powder were placed in two porcelain boats respectively and wrapped with a piece of tin foil. Then, they were directly transferred into a tubular furnace filled with argon and heated to 400°C at a heating rate of 2°C / min and maintained for 2 h. After the reaction was completed, the temperature was naturally lowered to prepare the ANDC@SnSSe@C composite electrode material.
[0049] Example 2
[0050] 1) Preparation of hollow tire-shaped carbon materials
[0051] The Aspergillus niger spores were ultrasonically treated in deionized water, cleaned and dried. 5 g of the dried Aspergillus niger spores were placed in a porcelain boat and wrapped with tin foil. Then, the boat was transferred into a high-temperature tube furnace protected by Ar atmosphere and heated at 5 °C / min. - The temperature was raised to 700°C at a heating rate and kept for 2 h, and finally naturally cooled to room temperature to obtain Aspergillus niger spore-derived hollow tire-shaped carbon material (ANDC).
[0052] 2) Preparation of ANDC@SnS2 precursor
[0053] 0.71 g of SnCl4·4H2O and 0.60 g of thioacetamide (TAA) were dissolved in 70 ml of isopropanol solution, and the mixture was stirred evenly for half an hour to obtain a mixed solution. Then 0.3 g of ANDC prepared in step 1) was added to the mixed solution, and the mixture was ultrasonicated for half an hour to obtain a suspension. The suspension was then transferred to a 100 ml high pressure reactor and reacted at 180°C for 6 hours. After the reaction was completed, the mixture was naturally cooled. The product was washed three times with deionized water and anhydrous ethanol in turn, and dried in a vacuum drying oven at 80°C for 8 hours to obtain ANDC@SnS2 material.
[0054] 3) Preparation of ANDC@SnS2@G composites
[0055] Take 0.3 g of the ANDC@SnS2 precursor prepared in step 2) and disperse it in 60 ml of 0.075 M glucose aqueous solution and ultrasonically stir it for 30 min. Then transfer it to a 100 ml high-pressure reactor and react it at 180 ° C for 12 h. After the reaction is completed, cool it naturally. Then, wash the product with deionized water and anhydrous ethanol three times in sequence, and dry it in a vacuum drying oven at 80 ° C for 8 h to obtain ANDC@SnS2@G material.
[0056] 4) Preparation of ANDC@SnS@C composites
[0057] The ANDC@SnS2@G material obtained in step 3) was placed inside a porcelain boat and wrapped with tin foil, and then transferred into a high-temperature tube furnace protected by Ar atmosphere. The temperature was then raised to 500°C at a heating rate of 2°C / min and kept at that temperature for 2h, and finally cooled naturally to room temperature to obtain an ANDC@SnS@C composite material.
[0058] 5) Preparation of ANDC@SnSSe@C composites
[0059] Take 0.2 g of ANDC@SnS@C obtained in step 4) and 0.8 g of selenium powder, respectively, and place them in two porcelain boats and wrap them with a piece of tin foil. Then, transfer them directly into a tubular furnace filled with argon and heat them to 400°C at a heating rate of 2°C / min and maintain for 2 h. After the reaction is completed, cool them naturally to obtain an ANDC@SnSSe@C composite electrode material.
[0060] Example 3
[0061] 1) Preparation of hollow tire-shaped carbon materials
[0062] The Aspergillus niger spores were ultrasonically treated in deionized water, cleaned and dried, and 5 g of the dried Aspergillus niger spores were placed inside a porcelain boat and wrapped with tin foil, and then transferred to a high-temperature tube furnace protected by Ar atmosphere. The temperature was then raised to 700°C at a heating rate of 5°C / min and kept for 2 hours, and finally cooled naturally to room temperature to obtain the Aspergillus niger spore-derived hollow tire-shaped carbon material (ANDC).
[0063] 2) Preparation of ANDC@SnS2 precursor
[0064] 0.596 g of SnCl4·4H2O and 0.131 g of thioacetamide (TAA) were dissolved in 70 ml of ethylene glycol solution and stirred evenly for half an hour to obtain a mixed solution; then 0.3 g of ANDC prepared in step 1) was added to the mixed solution and ultrasonicated for half an hour; then it was transferred to a 100 ml high pressure reactor and reacted at 180°C for 6 hours. After the reaction was completed, it was naturally cooled, and the obtained product was washed with deionized water and anhydrous ethanol three times in sequence, and dried in a vacuum drying oven at 80°C for 8 hours to obtain ANDC@SnS2 material.
[0065] 3) Preparation of ANDC@SnS2@G composites
[0066] 0.3 g of ANDC@SnS2 precursor prepared in step 2) was dispersed in 60 ml of 0.075 M glucose aqueous solution and ultrasonically stirred for 30 min to obtain a suspension, and then the suspension was transferred to a 100 ml high-pressure reactor and reacted at 180 ° C for 12 h. After the reaction was completed, it was naturally cooled. The obtained product was washed three times with deionized water and anhydrous ethanol in sequence, and dried in a vacuum drying oven at 80 ° C for 8 h to obtain ANDC@SnS2@G material.
[0067] 4) Preparation of ANDC@SnS@C composites
[0068] The ANDC@SnS2@G material obtained in step 3) was placed inside a porcelain boat and wrapped with tin foil, then transferred into a high-temperature tube furnace protected by Ar atmosphere, and then the temperature was raised to 500°C at a heating rate of 2°C / min and kept for 2h, and finally naturally cooled to room temperature to obtain an ANDC@SnS@C composite material.
[0069] 5) Preparation of ANDC@SnSSe@C composites
[0070] 0.2 g of ANDC@SnS@C obtained in step 4) and 0.8 g of selenium powder were placed in two porcelain boats respectively and wrapped with a piece of tin foil. Then, they were directly transferred into a tubular furnace filled with argon and heated to 400°C at a heating rate of 2°C / min and maintained for 2 h. After the reaction was completed, the temperature was naturally lowered to prepare the ANDC@SnSSe@C composite electrode material.
[0071] Example 4
[0072] 1) Preparation of hollow tire-shaped carbon materials
[0073] 5 g of Aspergillus niger spores were placed inside a porcelain boat and wrapped with tin foil, then transferred into a high-temperature tube furnace protected by Ar atmosphere, and the temperature was raised to 700 °C at a heating rate of 5 °C / min and kept for 2 h, and finally naturally cooled to room temperature to obtain Aspergillus niger spore-derived hollow tire-shaped carbon material (ANDC).
[0074] 2) Preparation of ANDC@SnS2 precursor
[0075] 0.385 g of SnCl2·2H2O and 0.056 g of sublimed sulfur were dissolved in 70 ml of isopropanol solution and stirred evenly for half an hour to obtain a mixed solution; then 0.3 g of ANDC prepared in step 1) was added to the mixed solution and ultrasonicated for half an hour; then it was transferred to a 100 ml high pressure reactor and reacted at 180°C for 12 hours. After the reaction was completed, it was naturally cooled, and the obtained product was washed with deionized water and anhydrous ethanol three times in sequence, and dried in a vacuum drying oven at 80°C for 8 hours to obtain ANDC@SnS2 material.
[0076] 3) Preparation of ANDC@SnS2@G composites
[0077] 0.3 g of the ANDC@SnS2 precursor prepared in step 2) was dispersed in 60 ml of a 0.075 M glucose aqueous solution and ultrasonically stirred for 30 min to obtain a suspension. The suspension was then transferred to a 100 ml high pressure reactor and reacted at 180 ° C for 12 h. After the reaction was completed, the mixture was naturally cooled. The product was washed three times with deionized water and anhydrous ethanol in sequence and dried in a vacuum drying oven at 80 ° C for 8 h to obtain ANDC@SnS2@G material.
[0078] 4) Preparation of ANDC@SnS@C composites
[0079] The ANDC@SnS2@G material obtained in step 3) was placed inside a porcelain boat and wrapped with tin foil, then transferred into a high-temperature tube furnace protected by Ar atmosphere, and then the temperature was raised to 500°C at a heating rate of 2°C / min and kept for 2h, and finally naturally cooled to room temperature to obtain an ANDC@SnS@C composite material.
[0080] 5) Preparation of ANDC@SnSSe@C composites
[0081] 0.2 g of ANDC@SnS@C obtained in step 4) and 0.8 g of selenium powder were placed in two porcelain boats respectively and wrapped with a piece of tin foil. Then, they were directly transferred into a tubular furnace filled with argon and heated to 400°C at a heating rate of 2°C / min and maintained for 2 h. After the reaction was completed, the temperature was naturally lowered to prepare the ANDC@SnSSe@C composite electrode material.
[0082] Example 5
[0083] 1) Preparation of hollow tire-shaped carbon materials
[0084] The Aspergillus niger spores were ultrasonically treated, cleaned and dried in deionized water. 5 g of the dried Aspergillus niger spores were placed inside a porcelain boat and wrapped with tin foil. They were then transferred into a high-temperature tube furnace protected by an Ar atmosphere. The temperature was then raised to 700°C at a heating rate of 5°C / min and kept for 2 h. Finally, the temperature was naturally cooled to room temperature to obtain a hollow tire-shaped carbon material (ANDC) derived from Aspergillus niger spores.
[0085] 2) Preparation of ANDC@SnS2 precursor
[0086] 0.596 g of SnCl4·4H2O and 0.131 g of thiourea were dissolved in 70 ml of isopropanol solution and stirred evenly for half an hour to obtain a mixed solution; then 0.3 g of ANDC prepared in step 1) was added to the mixed solution and ultrasonicated for half an hour; then it was transferred to a 100 ml high-pressure reactor and reacted at 180°C for 6 hours. After the reaction was completed, it was naturally cooled, and the obtained product was washed with deionized water and anhydrous ethanol three times in sequence, and dried in a vacuum drying oven at 80°C for 8 hours to obtain ANDC@SnS2 material.
[0087] 3) Preparation of ANDC@SnS2@G composites
[0088] 0.3 g of the ANDC@SnS2 precursor prepared in step 2) was dispersed in 60 ml of a 0.075 M glucose aqueous solution and ultrasonically stirred for 30 min to obtain a suspension. The suspension was then transferred to a 100 ml high pressure reactor and reacted at 180 ° C for 12 h. After the reaction was completed, the mixture was naturally cooled. The product was washed three times with deionized water and anhydrous ethanol in sequence and dried in a vacuum drying oven at 80 ° C for 8 h to obtain ANDC@SnS2@G material.
[0089] 4) Preparation of ANDC@SnS@C composites
[0090] The ANDC@SnS2@G material obtained in step 3) was placed inside a porcelain boat and wrapped with tin foil, then transferred into a high-temperature tube furnace protected by Ar atmosphere, and then the temperature was raised to 500°C at a heating rate of 2°C / min and kept for 2h, and finally naturally cooled to room temperature to obtain an ANDC@SnS@C composite material.
[0091] 5) Preparation of ANDC@SnSSe@C composites
[0092] 0.2 g of ANDC@SnS@C obtained in step 4) and 0.8 g of selenium powder were placed in two porcelain boats respectively and wrapped with a piece of tin foil. Then, they were directly transferred into a tubular furnace filled with argon and heated to 400°C at a heating rate of 2°C / min and maintained for 2 h. After the reaction was completed, the temperature was naturally lowered to prepare the ANDC@SnSSe@C composite electrode material.
[0093] Example 6
[0094] 1) Preparation of hollow tire-shaped carbon materials
[0095] The Aspergillus niger spores were ultrasonically treated in deionized water, cleaned, and dried. 5 g of the dried Aspergillus niger spores were placed in a porcelain boat and wrapped with tin foil. The boat was then transferred into a high-temperature tube furnace protected by Ar atmosphere and heated at 5 ° min. -1 The temperature was raised to 700°C at a heating rate and kept for 2 h, and finally naturally cooled to room temperature to obtain Aspergillus niger spore-derived hollow tire-shaped carbon material (ANDC).
[0096] 2) Preparation of ANDC@SnS2 precursor
[0097] 0.596 g of SnCl2·2H2O and 0.131 g of thiourea were dissolved in 70 ml of ethylene glycol solution and stirred evenly for half an hour to obtain a mixed solution; then 0.3 g of ANDC prepared in step 1) was added to the mixed solution and ultrasonicated for half an hour; then it was transferred to a 100 ml high pressure reactor and reacted at 180°C for 12 hours. After the reaction was completed, it was naturally cooled, and the obtained product was washed with deionized water and anhydrous ethanol three times in sequence, and dried in a vacuum drying oven at 80°C for 8 hours to obtain ANDC@SnS2 material.
[0098] 3) Preparation of ANDC@SnS2@G composites
[0099] 0.3 g of the ANDC@SnS2 precursor prepared in step 2) was dispersed in 60 ml of a 0.075 M glucose aqueous solution and ultrasonically stirred for 30 min to obtain a suspension. The suspension was then transferred to a 100 ml high pressure reactor and reacted at 180 ° C for 12 h. After the reaction was completed, the mixture was naturally cooled. The product was washed three times with deionized water and anhydrous ethanol in sequence and dried in a vacuum drying oven at 80 ° C for 8 h to obtain ANDC@SnS2@G material.
[0100] 4) Preparation of ANDC@SnS@C composites
[0101] The ANDC@SnS2@G material obtained in step 3) was placed inside a porcelain boat and wrapped with tin foil, then transferred into a high-temperature tube furnace protected by Ar atmosphere, and then the temperature was raised to 500°C at a heating rate of 2°C / min and kept for 2h, and finally naturally cooled to room temperature to obtain an ANDC@SnS@C composite material.
[0102] 5) Preparation of ANDC@SnSSe@C composites
[0103] 0.2 g of ANDC@SnS@C obtained in step 4) and 0.8 g of selenium powder were placed in two porcelain boats respectively and wrapped with a piece of tin foil. Then, they were directly transferred into a tubular furnace filled with argon and heated to 400°C at a heating rate of 2°C / min and maintained for 2 h. After the reaction was completed, the temperature was naturally lowered to prepare the ANDC@SnSSe@C composite electrode material.
[0104] Example 7
[0105] 1) Preparation of hollow tire-shaped carbon materials
[0106] The Aspergillus niger spores were ultrasonically treated, cleaned and dried in deionized water. 5 g of the dried Aspergillus niger spores were placed inside a porcelain boat and wrapped with tin foil. They were then transferred into a high-temperature tube furnace protected by an Ar atmosphere. The temperature was then raised to 700°C at a heating rate of 5°C / min and kept for 2 h. Finally, the temperature was naturally cooled to room temperature to obtain a hollow tire-shaped carbon material (ANDC) derived from Aspergillus niger spores.
[0107] 2) Preparation of ANDC@MoS2 precursor
[0108] Dissolve 0.215g of Na2MoO4·2H2O and 0.31g of thioacetamide in 60ml of deionized water, stir evenly for half an hour to obtain a mixed solution; then add 0.3g of ANDC prepared in step 1) into the mixed solution and ultrasonicate for half an hour; then transfer it to a 100ml high-pressure reactor and react at 200℃ for 24h. After the reaction is completed, cool it naturally, wash the product with deionized water and anhydrous ethanol three times in turn, and dry it in a vacuum drying oven at 80℃ for 8h to obtain ANDC@MoS2 material.
[0109] 3) Preparation of ANDC@MoS2@PDA composites
[0110] 0.3 g of ANDC@SnS2 precursor prepared in step 2) was dispersed in 60 ml of 10 mM Tris aqueous solution with a pH value of 8.0-8.5 and ultrasonically stirred for 30 min. Then 0.15 g of dopamine was added and stirred at room temperature for 6 h. After the reaction, the product was washed three times with deionized water and anhydrous ethanol in sequence and dried in a vacuum drying oven at 80 °C for 8 h to obtain ANDC@MoS2@PDA material.
[0111] 4) Preparation of ANDC@MoS2@C composites
[0112] The ANDC@MoS2@PDA material prepared in step 3) was placed inside a porcelain boat and wrapped with tin foil, then transferred into a high-temperature tube furnace protected by Ar atmosphere, and then the temperature was raised to 800°C at a heating rate of 2°C / min and kept for 2h, and finally naturally cooled to room temperature to obtain an ANDC@MoS2@C composite material.
[0113] 5) Preparation of ANDC@MoSSe@C composites
[0114] 0.2 g of ANDC@SnS@C obtained in step 4) and 0.8 g of selenium powder were placed in two porcelain boats respectively and wrapped with a piece of tin foil. Then, they were directly transferred into a tubular furnace filled with argon and heated to 400°C at a heating rate of 2°C / min and maintained for 2 h. After the reaction was completed, the temperature was naturally lowered to prepare the ANDC@MoSSe@C composite material.
[0115] Example 8
[0116] 1) Preparation of hollow tire-shaped carbon materials
[0117] The Aspergillus niger spores were ultrasonically treated, cleaned and dried in deionized water. 5 g of the dried Aspergillus niger spores were placed inside a porcelain boat and wrapped with tin foil. They were then transferred into a high-temperature tube furnace protected by Ar atmosphere. The temperature was then increased to 700°C at a heating rate of 5°C / min and kept for 2 h. Finally, the temperature was naturally cooled to room temperature to obtain a hollow tire-shaped carbon material (ANDC) derived from Aspergillus niger spores.
[0118] 2) Preparation of ANDC@WS2 precursor
[0119] 0.5 g Na2WO4·2H2O, 0.5 g thioacetamide and 0.5 g NaBH4 were dissolved in 60 ml aqueous solution and stirred evenly for half an hour to obtain a mixed solution; then 0.3 g ANDC prepared in step 1) was added to the mixed solution and ultrasonicated for half an hour; then it was transferred to a 100 ml high pressure reactor and reacted at 220°C for 12 hours. After the reaction was completed, it was naturally cooled, and the obtained product was washed three times with deionized water and anhydrous ethanol in sequence, and dried in a vacuum drying oven at 80°C for 8 hours to obtain ANDC@WS2 material.
[0120] 3) Preparation of ANDC@WS2@PPy composites
[0121] 0.3 g of ANDC@SnS2 precursor prepared in step 2) was dispersed in 50 ml of deionized water and ultrasonically stirred for 30 min, and then 0.5 g of sodium dodecylbenzenesulfonate, 0.4 g of FeCl3 and 0.2 ml of pyrrole monomer were added in sequence and stirred at room temperature for 5 h. After the reaction, the product was washed three times with deionized water and anhydrous ethanol in sequence, and dried in a vacuum drying oven at 80 °C for 8 h to obtain ANDC@WS2@PPy material.
[0122] 4) Preparation of ANDC@WS2@C composites
[0123] The ANDC@WS2@PPy material prepared in step 3) was placed inside a porcelain boat and wrapped with tin foil, then transferred into a high-temperature tube furnace protected by Ar atmosphere, and then the temperature was raised to 800°C at a heating rate of 2°C / min and kept for 2 h, and finally naturally cooled to room temperature to obtain an ANDC@WS2@C composite material.
[0124] 5) Preparation of ANDC@WSSe@C composites
[0125] 0.2 g of ANDC@WS2@C obtained in step 4) and 0.8 g of selenium powder were placed in two porcelain boats respectively and wrapped with a piece of tin foil. They were then directly transferred into a tubular furnace filled with argon. The temperature was then increased to 400°C at a heating rate of 2°C / min and maintained for 2 h. After the reaction was completed, the temperature was naturally lowered to obtain an ANDC@WSSe@C composite electrode material.
[0126] 2. Performance Testing
[0127] 1. The morphology of the Aspergillus niger spores and the tire-shaped carbon material after high temperature carbonization in Example 1 was observed under a scanning microscope and a projection microscope. The results are as follows: Figure 1 shown.
[0128] Depend on Figure 1 a and Figure 1b It can be seen that a large number of Aspergillus niger spores are monodisperse and have a tire-like biconcave morphology. At the same time, the surface of Aspergillus niger spores is relatively smooth. After high-temperature carbonization, the tire-like structure of Aspergillus niger spores is still well maintained, but the surface of the tire-like carbon material has obvious wrinkles and grooves compared to Aspergillus niger spores, with an average diameter of 3μm ( Figure 1 c and Figure 1 d). And the tire-shaped carbon material has an obvious hollow structure ( Figure 1 e and Figure 1 f).
[0129] 2. The morphology of ANDC@SnS2 and ANDC@SnS@C electrode materials prepared in Example 1 was observed under a scanning electron microscope. Figure 2 shown.
[0130] Depend on Figure 2 As can be seen from a and 2b, after the tire-shaped carbon material undergoes hydrothermal reaction, a large number of SnS2 nanosheets grow evenly on the surface of ANDC, forming a hollow biconcave structure wrapped by nanosheets. After further coating with a glucose-derived carbon layer, the hollow biconcave structure wrapped by the nanosheets remains well maintained without obvious morphological changes ( Figure 2 c and 2d).
[0131] 3. The morphology of the ANDC@SnSSe@C composite electrode material prepared in Example 1 was observed under a scanning electron microscope and a transmission electron microscope, respectively. The results are as follows: Figure 3 shown.
[0132] Depend on Figure 3 a and Figure 3 b It can be seen that after the ANDC@SnS@C material is treated with high-temperature selenization, the ANDC@SnSSe@C obtained maintains a morphology that is almost identical to that of the ANDC@SnS2 precursor sample, and a large number of nanosheets are still tightly wrapped in the hollow double-concave tire-like carbon structure, without obvious agglomeration of nanosheets or structural collapse ( Figure 3 c) From Figure 3 d It can be seen that in the area of about 10 nm, clear lattice fringes with a lattice spacing of 0.323 nm are displayed, corresponding to the (100) crystal plane of SnSSe.
[0133] 4. The ANDC@SnSSe@C electrode material prepared in Example 1 was subjected to X-ray diffraction, X-ray photoelectron spectroscopy, thermogravimetric analysis and paramagnetic resonance spectroscopy analysis. The results are as follows: Figures 4 to 6 shown.
[0134] from Figure 4It can be seen from the X-ray diffraction pattern that all crystal faces of the ANDC@SnSSe@C electrode material prepared in this embodiment can well match the standard SnSSe phase, similar to a hexagonal crystal.
[0135] from Figure 5 From the thermogravimetric analysis of a, we can see that there is a mass loss from room temperature to 200°C, which is mainly caused by the volatilization of the attached water inside the sample; the mass loss from 200°C to 700°C is due to the reaction of S, Se and C with oxygen in the air to produce SO2, SeO2 and CO2 gases; and the final stability at 700°C is due to the production of SnO2. Through the above data analysis, the mass percentage of SnSSe in ANDC@SnSSe@C electrode material is about 40.9%. Figure 5 The electron paramagnetic resonance spectrum of b shows the presence of a large number of defects in the ANDC@SnSSe@C electrode material, and the abundant crystal defects formed in situ inside the metal sulfide selenide nanosheets can not only serve as convenient Na + Diffusion sites to ensure Na + It not only promotes the rapid insertion process of the intermediates, but also acts as a propellant for the nucleation process of the intermediates in the initial transformation state by effectively reducing the Gibbs free energy.
[0136] from Figure 6 It can be seen from the X-ray photoelectron spectrum that the ANDC@SnSSe@C electrode material is mainly composed of Sn, S, Se, C and five elements.
[0137] 3. Application of ANDC@SnSSe@C composite electrode materials in sodium ion batteries
[0138] The ANDC@SnSSe@C electrode material prepared in Example 1 was taken as the negative electrode material and mixed with Ketjen black and CMC binder in a mass percentage of 60:30:10, and then an appropriate amount of deionized water was added, ground into a paste in an agate mortar, and coated on a copper foil with a diameter of 13 mm, and then the copper foil was vacuum dried at 80°C for 12 h to obtain the negative electrode sheet of the sodium ion battery, which was then transferred to an argon-filled glove box for assembly of button batteries. The button battery model was CR2032, the metal sodium sheet was used as the counter electrode, the diaphragm was glass fiber, and the electrolyte was 1 mol / L NaCF3SO3 solution (the solvent was diethylene glycol dimethyl ether solution).
[0139] 1. Cyclic voltammetry (CV) tests were performed on the CR2032 button cells assembled with the ANDC@SnSSe@C electrode materials at different scan rates of 0.2 to 2.0 mV / s (electrochemical workstation CHI-660E, voltage range 0.01 to 3.0 V, the same below). The results are as follows: Figure 7 shown.
[0140] As can be seen from the figure, all the CV curves obtained detected the presence of 6 redox peaks, and the peak current gradually increased with the increase of the scan rate. In addition, as the scan rate increases, the curve shape remains good, indicating that ANDC@SnSSe@C material has good rate performance and small polarizability.
[0141] 2. The CR2032 button cells assembled with the ANDC@SnSSe@C electrode materials were heated to 0.2-20.0A g -1 The discharge capacity was measured under the current density condition (Land 2001A test system, voltage range 0.01 ~ 3.0V), the results are as follows Figure 8 shown.
[0142] It can be seen from the figure that when the current density is 0.2, 0.5, 1.0, 2.0, 5.0, 10.0 and 20.0A g -1 When the discharge capacities are 638.2, 516.2, 455.1, 409.6, 345.4, 292.8 and 235.4 mAh g -1 When the current density gradually recovered to 0.2A g -1 When the capacity is restored to 652.1mAh g -1 , and its capacity retention rate exceeds 100%, indicating that the ANDC@SnSSe@C electrode material has excellent rate performance.
[0143] 3. The CR2032 button cell assembled with the ANDC@SnSSe@C electrode material was heated to 1.0A g -1 The cycle stability test was carried out at a current density of Fig. 9 shown.
[0144] from Fig. 9 As can be seen from a, the initial charge and discharge capacities of the ANDC@SnSSe@C electrode materials prepared in the present invention are 641.9 mAh g -1 and 509.3mAh g -1 , the corresponding initial Coulomb efficiency is 79.3%. Fig. 9 As can be seen in b, after the electrode has been cycled 120 times, its discharge capacity is still 416.4 mAh g -1 , the capacity retention is 64.9% of the initial discharge capacity, indicating that the material has a large specific capacity and good cycle stability.
[0145] 4. The CR2032 button cell assembled with the ANDC@SnSSe@C electrode material was heated at 20.0A g -1The cycle stability test was carried out at a current density of Fig.10 shown.
[0146] It can be seen from the figure that the initial discharge capacity of the ANDC@SnSSe@C electrode material prepared by the present invention is 398.5 mAh g -1 After 2000 cycles, the discharge capacity is still 293.0 mAh g -1 The average capacity decay rate per cycle is only 0.05%, indicating that the material still has good structural stability and cycle life at ultra-high rates.
[0147] 5. The above ANDC@SnSSe@C electrode material and the positive electrode material Na3V2(PO4)3@C were assembled into a CR2032 button-type full battery, and its cycle life and rate performance were tested. The results are as follows Fig.11 shown.
[0148] Depend on Fig.11 It can be seen that the full battery is at 1.0A g -1 When charged and discharged at a current density of , the initial charge and discharge capacities are 659.9 and 648.3 mAh g -1 , the initial Coulombic efficiency exceeds 100%. Fig.11 As can be seen in b, after the electrode has been cycled 100 times, its discharge capacity is still 243.3 mAh g -1 .from Fig.11 c and 11d, it can be seen that when the current density is 0.2, 0.5, 1.0, 1.5, 3.0 and 5.0 A g -1 When the discharge capacities are 622.6, 492.6, 430.7, 375.1, 275.4 and 180.1 mAh g -1 When the current density gradually recovered to 0.2A g -1 When the capacity is restored to 490.9mAh g -1 , and its capacity retention rate exceeds 78.8%, indicating that the ANDC@SnSSe@C of the present invention has great commercial application prospects.
[0149] It should be noted that the composite electrode materials prepared in Examples 2 to 8 also have good and cycle-stable electrochemical properties, which are not listed here one by one.
[0150] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A hollow tire-shaped carbon material composite transition metal sulfide selenide electrode material, characterized in that: The invention comprises a carbon skeleton with a three-dimensional hollow tire-like structure derived from Aspergillus niger spores and a transition metal sulfide selenide nanosheet material loaded on the carbon skeleton, wherein the outer layer of the nanosheet material is coated with a carbon layer, and the outer coated carbon layer is a carbon layer derived from glucose, polypyrrole or polydopamine; the electrode material has a chemical composition represented by ANDC@MSSe@C, wherein ANDC is a hollow tire-like carbon skeleton derived from Aspergillus niger, and M is a metal element Sn, Mo or W.
2. A method for preparing an electrode material of a hollow tire-shaped carbon material composite with a transition metal sulfide selenide as claimed in claim 1, characterized in that: The steps include: 1) ultrasonically treating Aspergillus niger spores in deionized water, washing them, and drying them; 2) subjecting the Aspergillus niger spores obtained in step 1) to high-temperature carbonization treatment in a tubular furnace with a protective atmosphere, and cooling naturally after the reaction is completed to obtain a hollow tire-shaped carbon material ANDC derived from the Aspergillus niger spores; 3) placing the ANDC material obtained in step 2) in a solution containing a sulfur source and one of a tin source, a molybdenum source and a tungsten source and continuously stirring to obtain a mixed solution, then transferring the mixed solution to a high-temperature reactor for a high-temperature reaction, cooling naturally after the reaction is completed, and then washing the product with deionized water and anhydrous ethanol for multiple times and drying to obtain an ANDC@MS2 composite material; 4) adding the ANDC@MS2 composite material obtained in step 3) into an aqueous solution containing glucose and continuously stirring to obtain a suspension, then transferring the suspension into a high-pressure reactor for hydrothermal reaction, and naturally cooling after the reaction to obtain a product; or adding the ANDC@MS2 composite material obtained in step 3) to an aqueous solution containing dopamine or pyrrole, and continuously stirring the reaction at room temperature to obtain a product; 5) The product obtained in step 4) is washed with deionized water and anhydrous ethanol for multiple times and dried, and then the dried product is placed in a tube furnace with a protective atmosphere for high-temperature carbonization treatment. After the reaction is completed, the temperature is naturally lowered to obtain ANDC@MS x @C (x = 1 or 2) composite material; 6) ANDC@MS prepared in step 5) x @C and selenium powder are placed in a porcelain boat respectively and wrapped with a piece of tin foil, and then selenized in a protective atmosphere. After the reaction is completed, the temperature is naturally lowered to obtain the hollow tire-shaped carbon material composite transition metal sulfide selenide electrode material ANDC@MSSe@C.
3. The method for preparing the electrode material of the hollow tire-shaped carbon material composite transition metal sulfide selenide according to claim 2, characterized in that: The high temperature carbonization treatment described in step 2) is to increase the temperature to 500-1000°C at a heating rate of 1-20°C / min and then keep it warm for 0.5-10h; the temperature of the high temperature reaction described in step 3) is 180-220°C for 12-24h.
4. The method for preparing the electrode material of the hollow tire-shaped carbon material composite transition metal sulfide selenide according to claim 2, characterized in that: In step 3), the tin source is tin tetrachloride or stannous chloride; the molybdenum source is sodium molybdate or ammonium molybdate; the tungsten source is sodium tungstate or ammonium tungstate; the sulfur source is sublimated sulfur, thioacetamide or thiourea; when the tin source is added to the mixed solution, the solution is an organic solvent, and the organic solution is ethylene glycol or isopropanol; when the molybdenum source or tungsten source is added to the mixed solution, the solution is deionized water.
5. The method for preparing the electrode material of the hollow tire-shaped carbon material composite transition metal sulfide selenide according to claim 2, characterized in that: Step 3) The amount of ANDC added to the mixed solution is 1.0-10 mg / mL, and the molar ratio of the tin source, molybdenum source or tungsten source to the sulfur source is 1:2-1:
4.
6. The method for preparing the electrode material of the hollow tire-shaped carbon material composite transition metal sulfide selenide according to claim 2, characterized in that: In step 4), the concentration of glucose, dopamine or pyrrole in the aqueous solution is 0.02-0.1 M; the temperature of the hydrothermal reaction is 150-200° C., and the time is 6-24 h.
7. The method for preparing the electrode material of the hollow tire-shaped carbon material composite transition metal sulfide selenide according to claim 2, characterized in that: The high temperature carbonization treatment in step 5) is performed by heating the temperature to 500-800°C at a heating rate of 1-10°C / min and then keeping the temperature for 1-6 hours.
8. The method for preparing the electrode material of the hollow tire-shaped carbon material composite transition metal sulfide selenide according to claim 2, characterized in that: In step 6), the selenization treatment is carried out by heating the temperature to 350-450°C at a heating rate of 1-5°C / min and then keeping the temperature for 0.5-5h; the ANDC@MS x The mass ratio of @C to selenium powder is 1:1 to 1:
10.
9. The method for preparing the electrode material of the hollow tire-shaped carbon material composite transition metal sulfide selenide according to claim 2, characterized in that: The protective atmosphere is argon or nitrogen; the drying is carried out at 25-90° C. for 8-12 hours.
10. Use of the electrode material according to claim 1 or the electrode material prepared by the method according to any one of claims 3 to 9 in a sodium ion battery.
Citation Information
Patent Citations
A method for preparing and applying a metal sulfide / carbon composite electrode material
CN110600275B
A method for preparing transition metal sulfide nanocomposite electrode materials
CN112349889B
Preparation method of carbon / metal sulfide / carbon three-dimensional porous array composite electrode material for lithium-ion battery
CN108258225A
Preparation method of hollow molybdenum sulfide diselenide nanospheres
CN108373141A
Sulfur-mould spore carbon ball / phosphate composite material and preparation method and application thereof
CN109273676A
